Rekontruksi Penggunaan Teori Positivisme Hukum dalam Penegakan Tindak Pidana Korupsi di Indonesia - Riki Kristianto; Mardi Candra; Yanto Yanto (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The freedom of judges in handing down sentences for criminal acts of corruption often creates legal uncertainty. Judges are given the freedom to assess sentences in corruption cases based on punishment theory and happiness theory. Very often the imposition of sentences actually causes injustice because of the leniency given by the judge. Positivism basically comes from a philosophical school that borrows the views, methods and techniques of Natural Science in understanding reality (scientism). So, as a result, legal science is freed from hermeneutics and is required to follow the rules in order to achieve legal certainty. Therefore, this article tries to answer how to reconstruct the use of legal positivism theory in enforcing criminal acts of corruption in Indonesia. This research is a qualitative type of normative juridical research with secondary data from decision No.34/Pid.Sus-Tpk/2021/PN.Jkt.Pst. Based on the research results, it shows that the positivist thinking pattern should be used as a guide for judges as law enforcers in prosecuting criminal acts of corruption, so that criminal acts of corruption in Indonesia no longer receive leniency and provide legal certainty